Myocardial rupture and left ventricular pseudoaneurysm due to late STEMI presentation during the COVID-19 pandemic lockdown: a classical case report. Issue 7 (18th July 2021) - Banisauskaite, Audra; Velavan, Periaswamy; Hasleton, Jonathan; Mediratta, Neeraj; Arzanauskaite, Monika; Binukrishnan, Sukumaran
Abstract: Background: Left ventricular (LV) pseudoaneurysm is a serious and rare complication of myocardial infarction (MI). It occurs when an injured myocardial wall ruptures and is contained by overlying adherent pericardium or scar tissue, most commonly it develops in patients with late presentation of MI and delayed revascularization. Case summary: A 64-year-old man presented to the emergency department with intermittent central chest pain radiating to back and neck and increasing on deep inspiration, which was considered to be of musculoskeletal origin for a week, but worsened despite medications. Electrocardiography showed features of ST-elevation MI; a circumflex artery occlusion was found on coronary angiogram and angioplasty was performed. Cardiovascular magnetic resonance (CMR) revealed features of healed lateral wall rupture with adherent parietal pericardium and the patient was managed conservatively. Two months later the patient returned with severe chest pain; echocardiogram and cardiac computed tomography showed significant interval progression of the pseudoaneurysm. Aneurysmectomy was performed, after which the patient recovered and had none of the previous symptoms since. Follow-up CMR study revealed improvement of LV systolic function. Discussion: A rare case of post-infarction LV pseudoaneurysm was reported. Multimodality imaging helped to detect and to differentiate this complication from the true aneurysm and to follow it up and plan the treatment. Conservative treatment was not effective in this case as the pseudoaneurysm progressed; aneurysmectomy helped to improve LV systolic function.